Dark personality traits and sociosexual dynamics in Australian men and women: Two direct replications of Borráz-León & Rantala (2021). (October 2022) - Leslie-Evans, Madeline; Bartschi, Jessica G.; Allen, Mark S.
Abstract: Direct replication is essential to establish generalisability of effects and identify false positive results. This research presents two direct replications of a study that explored dark personality traits (Machiavellianism, narcissism, and psychopathy) as predictors of self-perceived attractiveness, mate value and number of sexual partners (sociosexual dynamics), in Finnish university students (Borráz-León & Rantala, 2021). In the current study, 304 university students (48 men, 250 women; Sample 1) and 507 Australian adults (164 men, 339 women; Sample 2) completed questionnaires assessing the same dark traits and sociosexual dynamics. Results showed that higher levels of narcissism were associated with higher self-perceived attractiveness and mate value in both samples (directly replicating findings of the original research). Inconsistent with findings from the original study, psychopathy had a negative association with perceived mate value (in both samples), and dark traits were unrelated to number of sexual partners. There was little evidence that findings were moderated by sex with similar associations observed for men and women. Overall, the findings of this research provide evidence that narcissism and psychopathy can predict some sociosexual outcomes in Australian adults, and might be of interest to clinicians working in areas related to romantic and sexual issues. Highlights: Men scored higher than women on narcissism and psychopathy. Narcissism positively predicted self-perceived attractiveness and mate value. Psychopathy negatively predicted self-perceived attractiveness and mate value. Dark personality traits did not predict number of sexual partners. Most, but not all, findings replicated from the original study.